Cross-linguistic evidence for a non-distributive lexical meaning of conjunction - Flor, Enrico; Haslinger, Nina; Koopman, Hilda; Rosina, Eva; Roszkowski, Magdalena; Schmitt, Viola (Proceedings of the Amsterdam Colloquium, 2025)
This paper investigates the lexical meaning of elements like English and (‘coord’) in conjunctions with individual-denoting conjuncts by considering cross-linguistic form-function correlations. We present two generalizations concerning the correspondence between distributive readings and formal markedness both inside and outside the coordinate structure. We argue that they suggest that the cross-linguistic lexical meaning of coord is non distributive and that distributivity is introduced by additional operators. We then discuss how existing semantic treatments of coordinate structures could be adapted to yield a compositional analysis of the cross-linguistic facts.